2021
DOI: 10.1038/s41598-021-95491-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short- and long-term exposure to air pollution and meteorological factors on Meniere’s disease

Abstract: The association between air pollutants and Meniere’s disease has not been explored. The present study investigated the relationship between meteorological factors and air pollutants on Meniere’s disease. Participants, aged ≥ 40 years, of the Korean National Health Insurance Service-Health Screening Cohort were included in this study. The 7725 patients with Meniere’s disease were matched with 30,900 control participants. The moving average meteorological and air pollution data of the previous 7 days, 1 month, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Atmospheric pressure has been the best-described meteorological factor influencing MD attacks and tinnitus severity. Higher atmospheric pressure was positively correlated with the diagnosis of MD in a large-scale study analyzing over 7000 cases in South Korea [ 30 ]. Another prospective study identified increases in atmospheric pressure as risk factors for an MD episode on the following day [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric pressure has been the best-described meteorological factor influencing MD attacks and tinnitus severity. Higher atmospheric pressure was positively correlated with the diagnosis of MD in a large-scale study analyzing over 7000 cases in South Korea [ 30 ]. Another prospective study identified increases in atmospheric pressure as risk factors for an MD episode on the following day [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another link has been drawn between high relative humidity and increased frequency of Ménière’s attacks and tinnitus [ 21 , 30 ]. Our study found comparable results for tinnitus-related EVs independent of MD with extremely low relative humidity reducing EV risk within one day and a same-day increase in risk under extremely humid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in Korea revealed that O 3 exposure was associated with high incidence of Ménière's disease. Groundlevel O 3 in Wuhan is mainly produced by photochemical reactions of nitrogen oxides and volatile organic compounds (Choi et al, 2021). As the powerful inhaled oxidizing agent, studies showed that oxidative stress induced by O 3 exposure intimately linked with brain lipid peroxidation, neuroin ammation and subsequent neuron damage and impaired cerebral vascular endothelial injury (Cai et al, 2016;Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in Korea revealed that O 3 exposure was associated with high incidence of Ménière's disease. Groundlevel O 3 in Wuhan is mainly produced by photochemical reactions of nitrogen oxides and volatile organic compounds (Choi et al, 2021). As the powerful inhaled oxidizing agent, studies showed that oxidative stress induced by O 3 exposure intimately linked with brain lipid peroxidation, neuroin ammation and subsequent neuron damage and impaired cerebral vascular endothelial injury (Cai et al, 2016;Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%